Examining the Impact of Local Government Competencies on Regional Economic Revitalization: Does Social Trust Matter? - Jae-Kook Choi; Kuk-Kyoung Moon; Jaein Kim; Geon Jung (Systems)
This study aims to empirically analyze the direct effects of local government competencies on regional economic revitalization within the broader context of local communities and to investigate the moderating role of social trust in this relationship. Using panel data constructed from the 2012–2019 Seoul Survey provided by the Seoul Metropolitan Government and panel data from South Korea’s National Statistical Office, we employed feasible generalized least squares to account for potential heteroscedasticity and serial correlation. The results demonstrate that local government competencies positively impact regional economic vitality within local communities, with high levels of social trust among residents in these communities further strengthening this positive effect. This study highlights the theoretical importance of integrating resource-based and social capital theories to advance the field of urban regeneration and emphasizes the role of local communities in economic development. The findings suggest that even where local government competencies may be limited, a strong foundation of community social trust within local communities can drive economic revitalization. This underscores the need for central and local governments to actively enhance social trust within communities as a means of fostering sustainable economic growth.